Digital solution for supporting suicide prevention: human-centered, participatory development, usage trend analysis and adverse risk assessment - Kerstin Denecke; Caroline Gurtner; Gabriel Hess; François von Kaenel; Michael Durrer (BMC Digital Health)
Abstract Background Suicidal behavior is often the result of psychosocial crises and mental illness. Effective assessment and management of suicidal behavior are critical components of intervention. Digital tools, including self-management apps, offer a novel approach to help individuals actively manage their suicidal behavior. This study aims to develop and evaluate a digital application, the SERO app, tailored for suicide prevention with a focus on self-management and self-assessment for individuals at risk. It includes involvement of the relatives. Results The SERO app, result from a human-centered, participatory design development approach, provides an evidence-based platform for rapid self-assessment of suicide risk using the PRISM™-S method. It facilitates the creation and sharing of personalized safety plans, suggests activities based on these plans, and enhances community support by connecting users with supportive individuals such as relatives and crisis support organizations. Data is stored as HL7 FHIR® resources in a secure health database. Post-launch analysis has shown that the safety plan and self-assessment features are the most commonly used features. Conclusions While evidence-based practices are built into the SERO app, it is important to acknowledge that its use may lead to unintended consequences. In the future, we intend to implement countermeasures to mitigate potential misuse and minimize harm. Our findings suggest that early assessment of possible risks related to the interaction with a digital health intervention plays a critical role in ensuring patient safety, particularly in sensitive areas such as mental health.